Psicologia aplicada ao trabalho e ideologia da racionalidade tecnológica: um estudo sobre a atuação do psicólogo nas organizações - Guimarães, Denise Alves (2010)
This research aims to verify the general relationship between the psychologists practice in organizations and ideology of technological rationality. The sample of 106 psychologists working in the field of psychology applied to work in Belo Horizonte, Contagem and Betim, on which was applied a Likert scale, was validated by the author and consists of four subscales: the ideology of technological rationality; performance of psychologists; workers control and conception of work and worker. The contents of the statements are interdependent and based on discussions of authors of critical theory. The obtained results serve to confirm the general hypothesis that psychologists practice in organizations is significantly associated with the ideology of technological rationality, justified a) by the agreement of the subjects into a performance related to the maintenance and reproduction of interests of the administrated society (AP subscale - role of psychologists); b) by the balance between agreements and disagreements in relation to the demands of the production system on workers' control (subscale WC - workers' control), suggesting that the current difficulties of analysis and criticism of the immediate reality also express the contradictions of the current form of social organization. The results confirm neither the hypothesis that subjects adhere to the ideology of technological rationality (subscale TR - ideology of technological rationality) nor the hypothesis that psychologists tend to adhere to standards that characterize the administrated society in relation to the meaning of work, to the criteria of competence and suitability for the behavior of workers (subscale W conception of work and worker)